The linguo-stylistic analysis of creative elaborations in Aksel Bakunts’ “Mirhav” - Nersisyan, Narine (History and Culture, 2023)
For the first time, this article has conducted a comprehensive lingo-stylistic analysis of creative elaborations in A. Bakunts’ “Mirhav”. When preparing the final version, the great master of words has done the editing diligently by reaching the perfection of words and images, poemization of prose, excellent attractiveness and emotionality. The changes in the image system have strengthened the content persuasiveness, the ideological saturation of the narrative and helped to discover the rich world of human emotions, creating harmony between the real visual, auditory images and their emotional illusions.The perception and interpretation of the war of 1920 has certain parallels with the Artsakh war of 2020 (unreasonable overestimation of own forces and underestimation of the enemy's forces, search for traitors and culprits, etc.).
Keywords: Creative processing; original text; comparative investigation of versions; aesthetic appeal; enhancement of the idea; poeticization of prose speech; reinforcement of metaphor